Platformizing Islamic Political Legitimacy across the 2014-2024 Indonesian Election: Rearticulating Authority and Morality in Digital Democracy - Gumilar, Setia; Nurdin, Ahmad Ali; Rahman, M. Ridha Taufiq (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2026)
Digital platforms have structurally reconfigured the conditions under which Islamic parties produce and contest political legitimacy in electoral democracies. This article examines how platformization transformed the campaign discourse of two major Indonesian Islamic parties, PKS and PKB, across the 2014, 2019, and 2024 general elections. Using Facebook posts from the official accounts of PKS, PKB, and Kompas as an issue-control corpus, the study applies a qualitative, comparative, diachronic framework that integrates platformization theory, the hybrid media system perspective, Entman’s framing analysis, Fairclough’s Critical Discourse Analysis, and van Leeuwen’s legitimation theory. The findings demonstrate that Islamic party discourse became progressively platform-oriented across three electoral cycles, characterized by increasing hashtag adoption, modular slogans, and explicit calls to action. More significantly, the dominant legitimating resources shifted from organizational mobilization and procedural credibility in 2014, to religious endorsement and communal symbolism in 2019, to welfare claims and democratic ethics in 2024. These findings indicate that platformized Islamic politics in Indonesia constitutes selective rearticulation rather than de-Islamization, as the moral vocabulary of Islam is continuously reformulated into forms more compatible with platform legibility and mass electoral resonance.